A PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KEARIFAN LOKAL ISTANA RAJA AMARASI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI BANGUN RUANG DI KELAS VI SD NEGERI RETRAEN KABUPATEN KUPANG - Resti Rosmalinda Batmaro; Hingrida Margarita Anastasia Hendrik; Siprianus Tua (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Batmaro Resti, 2026. Development of Learning Media Based on the Local Wisdom of the King of Amarasi’s Palace to Improve Learning Outcomes for Grade VI Students at SD Negeri Retraen. Supervisor I: Hingrida M. A. Hendrik, S.Pd., B.Ed., M.M.; Supervisor II: Siprianus Tua, S.Pd., M.Pd..Primary School Teacher Education Study Program, Faculty of Teacher Training and Education, Universitas Citra Bangsa Kupang. This research is motivated by the limited use of learning media that incorporates elements of local wisdom. Furthermore, the limited use of learning media has resulted in students being less active and prone to boredom. This situation has led to a low level of student understanding regarding the topic of geometric solids. Therefore, there is a need for engaging learning media that connects mathematical concepts with local culture—specifically, the King of Amarasi’s Palace. This study aims to determine the feasibility, practicality, and effectiveness of the developed learning media—based on the local wisdom of the King of Amarasi’s Palace—in improving the learning outcomes of Grade VI students at SD Negeri Retraen in the mathematics subject area of ​​geometric solids. This study employs the Research and Development (R&D) method using the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). Data analysis involved both preliminary and final analysis techniques. The results indicate that the learning media—based on the local wisdom of the King of Amarasi Palace and designed for the 6th-grade mathematics topic of geometric solids at SD Negeri Retraen—is highly suitable for classroom use. Evaluations by experts, teachers, and students yielded high ratings: 98.33% from subject matter experts (categorized as